Vann, juss og samfunn rettigheter og regulering i utvikling - Bakken, Tor Haakon (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Society's use and management of water relies on professional expertise spanning diverse fields: from biology and technology to economics and law. This book examines current issues related to regulating water through chapters summarizing various sets of regulation as well as chapters that take a scientific deep dive into selected themes. The diversity of professional expertise is also reflected in the law aspect. We explore such subjects as surface runoff, natural disasters, drinking water, groundwater, salmon, hydropower, and human rights, as well as general impact assessment requirements and duty of knowledge in environmental law administration. A key objective of the book has been to provide an interdisciplinary understanding of the legal circumstances associated with water, and in addition, deliberate the pros and cons of some of the current regulations. This book will be particularly useful for those who in various ways support and facilitate procedures within the public sector at both the national and municipal levels. It will also be useful for private sector actors seeking familiarity with legal questions that can arise in relation to public administration and other private actors. From a broader perspective, we hope the book can help to throw light on conflicts between different interests and groups within society that occur, for example, when introducing fees, special injunctions against private actors, and requirements for knowledge basis. This book project is the result of legal research conducted at the Norwegian University of Life Sciences (NMBU) and is supplemented by national expertise in several areas. It has been edited by Steinar Taubøll, a professor at NMBU's Department of Property and Law. Taubøll has a background in both law and the natural sciences, and extensive experience with interdisciplinary work.